Electrochemically deposited nanocrystalline InSb thin films and their electrical properties. Issue 6 (20th January 2016) - Hnida, K. E.; Bäßler, S.; Mech, J.; Szaciłowski, K.; Socha, R. P.; Gajewska, M.; Nielsch, K.; Przybylski, M.; Sulka, G. D.
Abstract : Indium antimonide thin films were fabricated by pulse electrodeposition. Band gap widening due to quantum confinement (0.17 eV) and the Burstein–Moss effect (0.19 eV) was observed. The stoichiometric InSb films showed S coefficient values higher than those obtained by MOCVD. Abstract : We present an electrochemical route to prepare nanocrystalline InSb thin films that can be transferred to an industrial scale. The morphology, composition, and crystallinity of the prepared uniform and compact thin films with a surface area of around 1 cm 2 were investigated. The essential electrical characteristics such as conductivity, Seebeck coefficient, the type, concentration and mobility of charge carriers have been examined and compared with InSb nanowires obtained in the same system for electrochemical deposition (fixed pulse sequence, temperature, electrolyte composition, and system geometry). Moreover, obtained thin films show much higher band gap energy (0.53 eV) compared to the bulk material (0.17 eV) and InSb nanowires (0.195 eV).